Synthesis and Anti-Breast Cancer Activities of Substituted Quinolines - Shi, Aibin (2008)
Promising anti-breast cancer agents derived from substituted quinolines were discovered. The quinolines were readily synthesized in large scale from a sequence of reactions starting from 4-acetamidoanisole. The Michael addition product was isolated as the reaction intermediate in the ring closing reaction of 4-amino-5-nitro-2-(3-trifluoromethylphenyloxy)anisole with methyl vinyl ketone leading to 6-methoxy-4-methyl-8-nitro-5-(3-trifluoromethylphenyloxy)quinoline (14). The amino function of 8-amino-6-methoxy-4-methyl-5-(3-trifluoromethylphenyloxy)quinoline, prepared from 14, was connected to various side chains via alkylation with N-(3-iodopropyl)phthalimide, Michael addition with acrylonitrile, and reductive amination with various heterocycle carboxaldehydes, such as imidazole-4-carboxaldehyde, thiophene-2-carboxaldehyde, and 2-furaldehyde. Effects of the substituted quinolines on cell viability of T47D breast cancer cells using trypan blue exclusion assay were examined. The results showed that the IC(50) value of 6-methoxy-8-[(2-furanylmethyl)amino]-4-methyl-5-(3-trifluoromethylphenyloxy)quinoline is 16 ± 3 nM, the lowest IC(50) out of all the quinolines tested. IC(50) values of three other quinolines are in the nanomolar range, a desirable range for pharmacological testing.